Pemanfaatan Limbah Bonggol Jagung Sebagai Media Tanam Jamur di Masyarakat Desa Kawo Kecaman Pujut Kabupaten Lombok Tengah - Yeyen Riska Pramita; Munawir Sazali; Heri Murtawan (Bhakti: Jurnal Pengabdian Masyarakat, 2024)
The utilization of corn stalk waste for mushroom cultivation is one of the efforts to reduce agricultural waste, namely from corn commodities. In order for the cultivation of merang mushrooms to obtain maximum results, it is necessary to optimize it. Optimization carried out in the utilization of corn stalks is by providing assistance, and training through counseling, practice, and demonstrations including material preparation, medium formulation, making mushroom growth medium, and mushroom maintenance management. The purpose of this service is to increase community understanding of the utilization of corn stalk waste as a mushroom growing medium and as an alternative business for the people of Gilik Hamlet, Kawo Village, Pujut District, Central Lombok Regency in increasing their daily income. The method used in the implementation method in this community service activity begins with a location survey, information dissemination, training (hands-on practice), and mentoring. This community service activity was carried out in Gilik Hamlet, Kawo Village, Pujut District, Central Lombok Regency on Sunday, April 07, 2024 at 15:00 WITA-complete. The procedure for making mushrooms starts with preparing the cultivation site, making a mixture, placing and leveling the corn stalks in the cultivation site, then, watering it evenly with water and covering it with a tarpaulin to keep it moist and warm. The initial yield of harvesting corncob mushrooms ranges from four to five kilos in one harvest. These mushrooms can be harvested every afternoon. The mushroom marketing process is carried out online through WhatsApp and Facebook media. The marketing price of this mushroom ranges from 35-40 per kg.